Analysing the Condition of PT Indofood Sukses Makmur Tbk During 2020-2022 - Wantriani, Retno; Susanti, Neneng (Devotion : Journal of Research and Community Service, 2024)
During the period 2020 to 2022, the financial reports reported by PT Indofood Sukses Makmur Tbk illustrate that this company was able to survive during the pandemic when almost all companies experienced a decline in turnover, so that quite a few companies went out of business. A company's resilience in maintaining financial performance greatly influences the company's condition so that it remains viable and stable when the country's economy is not doing well. The aim of this research is to determine the condition of the company PT Indofood Sukses Makmur Tbk in the 2020-2022 period using descriptive quantitative research. The problem formulation in this research is the condition of PT Indofood Sukses Makmur Tbk based on ratio analysis, comparison ratio, common size ratio, time series ratio and bankruptcy ratio. The research results show that the ratio analysis shows that the company has more internal cash compared to other current assets. This cash was obtained from short-term and long-term bank loans as well as bonds payable. For the activity ratio, it is indicated that the company is experiencing problems in collecting receivables from its colleagues. For the profitability ratio, the company has not been able to generate profits in accordance with industry standards. Regarding the comparison ratio, in general the comparison value during the research period decreased, as did the time series ratio which experienced a decrease. Meanwhile, in the bankruptcy ratio, the company is indicated as bankrupt but is experiencing a slow increase.